Effect of Capital, Labor, Land Area, Distribution Patterns on Shallot Production in Uluere Sub-district - Nurdiana, Nurdiana (Cita konsultindo, 2023)
The objectives of this study are 1) To determine simultaneously the effect of capital, labor, land area, and distribution patterns on shallot production in Uluere District. 2) To determine partially the effect of capital, labor, land area, and distribution patterns on the income of shallot farmers in Uluere sub-district. This research uses quantitative descriptive research methods because in its implementation includes data, analysis, and interpretation of the meaning of the data obtained, the data used are primary and secondary data. There are 12 samples in this study then processed using SPSS 25 and analyzed using multiple linear regression analysis techniques. From the research results obtained: that the variables of capital, labor, land area, and distribution patterns simultaneously have a significant effect and are positively related to the level of shallot production in Uluere District. Capital and labor variables partially have a significant positive effect on shallot production, while land area and distribution patterns have a significant effect and have a real effect on the level of shallot production in Uluere District.